ChemInform Abstract: The Interpenetrated Three‐Dimensional Framework of a New Mixed Lithium/Ammonium Perchlorate Growth in a Gel Medium. Issue 29 (1st July 2013) - Walha, Siwar; Bouchaala, Mahmoud; Ben Salah, Abdelhamid
Abstract: Li9.41 (NH4 )0.59 ClO4 is synthesized by slow diffusion of aqueous lithium oxalate and ammonium oxalate dissolved in perchloric acid through agar agar gel at ambient temperature.